(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
Vaginal discharge is a common reproductive health problem experienced by women of reproductive age (WRA) and may be physiological or pathological in nature. Limited knowledge often makes WRA unable to distinguish between these conditions, thereby increasing the risk of health complications when pathological vaginal discharge is not properly managed. In Lubuk Pakam Pekan Village, limited access to reproductive health education and low awareness of preventive behaviors among WRA are still evident. This Community Service Program aimed to improve knowledge, attitudes, and preventive behaviors related to vaginal discharge among WRA through health mentoring based on the Health Belief Model (HBM), combined with the utilization of basil leaf (Ocimum basilicum) decoction as a local wisdom–based preventive approach. The program was implemented using an educative–participatory approach with a community-based health mentoring strategy. The target group consisted of 25 women aged 15–49 years in Lubuk Pakam Pekan Village. The intervention included HBM-based reproductive health education, mentoring on genital personal hygiene practices, and demonstrations of the preparation and use of basil leaf decoction. Evaluation was conducted using pre-test and post-test assessments to measure changes in knowledge, attitudes, and preventive behaviors. The results showed an increase in good knowledge from 36% to 84%, positive attitudes from 40% to 88%, and good preventive behaviors from 32% to 80%. In addition, participant engagement was high, and most WRA continued to practice preventive behaviors after the program concluded. It can be concluded that HBM-based health mentoring combined with the use of basil leaf decoction is effective in promoting sustainable preventive behaviors against vaginal discharge among women of reproductive age.